Access to banking services and poverty reduction: a state-wise assessment in India - Amit K. Bhandari (Institute for the Study of Labor (IZA), 2009)
Financial inclusion is the broad based delivery of banking and other financial services at affordable cost to the poorest sections of society. In India, financial inclusion emphasizes to include maximum number of people under formal financial systems. The most important part of financial services in a region is typically measured by number of people who have access to bank accounts. The present study investigates the drive to financial inclusion in the form of the growth in bank accounts of scheduled commercial banks and the changes in below poverty line population. The result suggests that the growth in bank accounts is not significantly associated with the reduction in below poverty line population across states. Providing banking services to maximum number of people is unsuccessful as a poverty reduction strategy. As a poverty reduction strategy, developing inclusive financial systems should give priority, which is financially and socially sustainable.
urn:nbn:de:101:1-20090513309
Keywords: G24; G21; I32; 330; Banking; financial inclusion; poverty; Finanzdienstleistung; Bankgeschäft; Versorgung; Armut; Armutspolitik; Indien